1997
DOI: 10.1007/pl00005005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of blockade of α1-adrenoceptors, β1-adrenoceptors and vasopressin V1A receptors on the cardiovascular effects of γ2-melanocyte-stimulating hormone (γ2-MSH)

Abstract: gamma 2-Melanocyte-stimulating hormone (gamma 2-MSH) and related melanotropins have been shown to have various cardiovascular effects, including acute, short-lasting increases in blood pressure (MAP) and heart rate (HR). gamma 2-MSH, administered intravenously, dose-dependently increased MAP and HR with an ED50 of approximately 30 nmol/kg and a maximal effect on MAP of approximately 55 mm Hg and on HR of around 70 beats per minute. Intravenous (i.v.) pretreatment with the alpha 1-adrenoceptor antagonist, prazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Injections of ␥-MSH intravenously or into a carotid artery result in a transient pressor and cardioaccelerator response that is due to central activation of sympathetic outflow. This may involve a vasopressinergic pathway, because it is blunted in Brattleboro rats lacking vasopressin (45), although not all observations are consistent with this (119). It likely also involves a neural circuit in the anteroventral region of the third ventricle, because lesions of this region reduced the pressor response to intravenous ␥-MSH (11).…”
Section: Cardiovascular Actions Of ␥-Mshsupporting
confidence: 50%
“…Injections of ␥-MSH intravenously or into a carotid artery result in a transient pressor and cardioaccelerator response that is due to central activation of sympathetic outflow. This may involve a vasopressinergic pathway, because it is blunted in Brattleboro rats lacking vasopressin (45), although not all observations are consistent with this (119). It likely also involves a neural circuit in the anteroventral region of the third ventricle, because lesions of this region reduced the pressor response to intravenous ␥-MSH (11).…”
Section: Cardiovascular Actions Of ␥-Mshsupporting
confidence: 50%
“…The absence of a direct effect on cardiovascular structures and the postulate of Gruber and Callahan (1989), which was further supported by the findings of others (Sun et al 1992;De Wildt et al 1993;Van Bergen et al 1997b) that the hemodynamic effects of γ 2 -MSH depend on an intact sympathetic nervous system led us to carry out a series of experiments to investigate possible modulating effects of the peptide at preganglionic or postganglionic level within the peripheral sympathetic nervous system. Previous studies have demonstrated that melanocortins structurally related to γ 2 -MSH, such as ACTH-(1-24), possess such a sympathetic nervous system-modulating property, which results, through activation of presynaptic ACTH (melanocortin) receptors, in a facilitation of noradrenaline release.…”
Section: Discussionmentioning
confidence: 81%
“…In addition to their e ects on the hormonal system, behaviour, temperature and feeding regulation, g-MSHs and in particular g 2 -MSH and its shorter fragment g 2 -MSH(6 ± 12) have strong e ects on the cardiovascular system (Callahan et al, 1985;Li et al, 1996;Sun et al, 1992;Van Bergen et al, 1995;1997a). Systemic administration of g 2 -MSH and g 2 -MSH(6 ± 12) to rats causes a dose-dependent increase in mean arterial pressure (MAP) and heart rate (HR).…”
Section: Introductionmentioning
confidence: 99%